DISAIN PENCIPTAAN FILM PAKASIAH BABIOLA - Muhammad Ritzky Saibi (Melayu Arts and Performance Journal, 2021)
Minang Creating the fictional film "Pakasiah Biola" departs from several parts of the film's elements, where the film, when viewed from a genre perspective, is divided into three parts, namely fiction films, documentary films, and experimental films. The choice of the fiction genre that the author makes here is because films with that genre have a very wide space in transforming ideas and space to realize the imaginative thoughts that the author gets when analyzing the script "Pakasiah Biola" either visually/cinematically or narratively. In the concept of the work of Pakasiah Biola that will be made, the artist creates a film based on Bazin's thinking, and there are 7 things that become elements of the realist film structure, which include: relatively simple stories, reallocation, real setting unprofessional actors, deep-focus, long-take and minimize editingKeywords: Pakasiah Violin; Fiction Movies; Fiction Genre.AbstrakMenciptakan film fiksi “Pakasiah Biola”, berangkat dari beberapa bagian unsur film, dimana film apabila ditinjau dari segi genre dibagi menjadi tiga bagian yaitu film fiksi, film dokumenter dan film experimental. Pilihan terhadap genre fiksi yang pengkarya lakukan disini karena dalam film dengan genre tersebut memiliki ruang yang sangat luas dalam mentransformasikan ide-ide dan ruang untuk merealisasikan pemikiran-pemikiran imajinatif yang pengkarya peroleh ketika menganalisa naskah “Pakasiah Biola” baik secara visual/cinematic ataupun secara naratif.Pada konsep garapan karya film Pakasiah Biola yang akan dibuat, pengkarya menciptakan film berdasarkan pemikiran Bazin terdapat 7 hal yang menjadi elemen struktur film realis, yang meliputi: relative simple strories, real location, real setting unprofessional actors, deep-fosus, longtake, dan minimize editingKata Kunci: Pakasiah Biola; Film Fiksi; Genre Fiksi.